Process Upgrading and Value Added in Community-Based Pottery Production: A Micro-Level Value Chain Analysis - Friesca Erwan; Nisrina Salsabila; Awal Aflizal Zubir (Winaya Inspirasi Nusantara Foundation, 2026)
Traditional pottery enterprises continue to face structural challenges that limit their ability to generate economic value, particularly in micro-scale, community-based settings where production relies heavily on manual techniques and tacit knowledge. These constraints often manifest in inefficient process design, uneven time allocation, and inconsistent quality control, all of which restrict value creation and weaken the economic resilience of artisans. Responding to these challenges, this study aims to examine how value is created within a traditional pottery production system and to assess whether targeted, context appropriate interventions can enhance value added without compromising artisanal identity. Using a production-oriented value chain approach, the research employs detailed observation, cost analysis, and semi structured interviews to map production activities and quantify value added across stages. This methodological combination enables a granular assessment of how specific production practices shape economic outcomes. The findings show that baseline value creation is weakly embedded in production activities and heavily dependent on extended labor input. Structural inefficiencies limit reinvestment capacity, particularly in drying and firing. However, targeted process improvements, including enhanced forming tools and controlled firing, significantly increased quality consistency and reduced defect rates. These interventions nearly doubled value added per production cycle while preserving traditional product characteristics. The study contributes to value chain scholarships by demonstrating the importance of production level granularity in informal manufacturing contexts. Practically, the results highlight the potential of modest, culturally aligned process improvements to strengthen productivity, income stability, and long-term sustainability in traditional craft industries.